2014
DOI: 10.3233/jad-131532
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Disease and Methanol Toxicity (Part 2): Lessons from Four Rhesus Macaques (Macaca mulatta) Chronically Fed Methanol

Abstract: A recently established link between formaldehyde, a methanol metabolite, and Alzheimer's disease (AD) pathology has provided a new impetus to investigate the chronic effects of methanol exposure. This paper expands this investigation to the non-human primate, rhesus macaque, through the chronic feeding of young male monkeys with 3% methanol ad libitum. Variable Spatial Delay Response Tasks of the monkeys found that the methanol feeding led to persistent memory decline in the monkeys that lasted 6 months beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…During aging, chronic accumulation of endogenous FA is thought to be a risk factor for sporadic age-related dementia [10, 28]. Furthermore, excess FA has been found to contribute to the pathological aggregation of amyloid fragments and tau hyperphosphorylation in normal adult mice and monkeys [29, 30]. More importantly, a direct intracerebroventricular injection of excess FA into animal models causes memory decline [1315].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During aging, chronic accumulation of endogenous FA is thought to be a risk factor for sporadic age-related dementia [10, 28]. Furthermore, excess FA has been found to contribute to the pathological aggregation of amyloid fragments and tau hyperphosphorylation in normal adult mice and monkeys [29, 30]. More importantly, a direct intracerebroventricular injection of excess FA into animal models causes memory decline [1315].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, using a FA detection kit, a two-fold increase in the levels of FA (0.016 mM) was found in the cerebrospinal fluid of monkeys given an intracerebroventricular injection of methanol [31], which induced cognitive impairments, AD-like amyloid plaques, and tau hyperphosphorylation [30]. Using HPLC-Fluo, endogenous concentrations of FA in human blood and urine were found to be approximately 0.08 and 0.03 mM, respectively [12, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Yang M et al reported that young male rhesus macaque fed with 3% methanol ad libitum for 6 months showed AD-like pathologies, including persistent memory decline, higher Tau phosphorylation, and Aβ depositions. 164 In addition, they found formaldehyde, rather than methanol or the methanol end product formic acid, led to Tau hyperphosphorylation in mouse embryonic cerebral cortex neurons and mouse neuroblastoma N2a cells. 165 The same group also reported that spatial working memory impairments, increased Tau phosphorylation and neuronal loss, accompanied by the presence of Aβ + neuritic-like plaques and NFT-like formations were observed in the brain from young rhesus macaques (5-8 years old) intracerebroventricularly injected formaldehyde for 12 months.…”
Section: Nhps: a Bridge Between Rodents And Humans?mentioning
confidence: 99%
“…Recently, a novel sAD NHP model induced by methanol and formaldehyde have been established. Yang M et al reported that young male rhesus macaque fed with 3% methanol ad libitum for 6 months showed AD‐like pathologies, including persistent memory decline, higher Tau phosphorylation, and Aβ depositions .…”
Section: Nhps: a Bridge Between Rodents And Humans?mentioning
confidence: 99%
“…Notably, recent experimental findings demonstrated that other mechanisms independent from A β could be responsible for cognitive decline of AD. In particular, it has been proposed that inducing hyperphosphorylation of tau could be involved in mechanisms of neurodegeneration . Unexpectedly, other substances like formaldehyde or mechanisms of D‐ribosylation, not involved in A β metabolism could trigger neuronal degeneration.…”
Section: Aβ42 As a Marker Of Experimentally Induced Impaired Neuronalmentioning
confidence: 99%